AN ANOMALOUS EUCRITE, DHOFAR 007, AND A POSSIBLE GENETIC RELATIONSHIP WITH MESOSIDERITES - Yamaguchi A.; Ebihara M.; Setoyanagi T. (My University, 2006)
We studied the texture, mineralogy, and bulk chemical composition of Dhofar 007, a basaltic achondrite. Dhofar 007 is a polymict breccia that is mostly composed of coarse-grained granular (CG) clasts with a minor amount of xenolithic components, such as a fragment of Mg-rich pyroxene. The coarse-grained, relict gabbroic texture, mineral chemistry, and bulk chemical data of the coarse-grained clast indicate that the CG clasts were originally a cumulate rock crystallized in a crust of the parent body. However, in contrast to monomict eucrites, the siderophile elements are highly enriched and could have been introduced by impact events. Dhofar 007 appears to have experienced a two-stage postcrystallization thermal history: rapid cooling at high temperatures and slow cooling at lower temperatures. The presence of pigeonite with closely spaced, fine augite lamellae suggests that this rock was cooled rapidly from higher temperatures (>0.5 °C/yr at ~1000 °C than typical cumulate eucrites. However, the presence of the cloudy zone in taenite and the Ni profile across the kamacite-taenite boundaries indicates that the cooling rate was very slow at lower temperatures (~1-10 °C/Myr at <600-700 °C). The slow cooling rate is comparable to those in mesosiderites and pallasites. The two-stage thermal history and the relative abundance of siderophile elements similar to those for metallic portions in mesosiderites suggest that Dhofar 007 is a large inclusion of mesosiderite. However, we cannot rule out a possibility that Dhofar 007 is an anomalous eucrite. © The Meteoritical Society, 2006.